HAK ASASI MANUSIA BAGI PENYANDANG DISABILITAS DALAM MENDAPAT PEKERJAAN YANG LAYAK TANPA ADANYA DISKRIMINASI - Pramadita Hasbullah; Rahayu Rahayu (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2018)
People with disabilities are a minority community in the world. Communities who consider that persons with disabilities have limitations that interfere with their activities, especially in working to make discrimination of the rights of people with disabilities. Governments in various countries of the world have issued various regulations that support the realization of the rights of people with disabilities, especially in getting a job. The purpose of writing this article is to find out how legal protection for people with disabilities who experience discrimination in the world of work. Type of writing using normative legal writing that produces descriptive data analysis. Government laws and regulations have been established to prohibit discrimination on the basis of disability of all forms of employment, but the unavailability of information services and lack of care for disability workers is still a hindrance.